Empirical Tests of the Existence of Industry Momentum on the Indonesian Stock Exchange - Verda, Irene Natalia (The Indonesian Capital Market Review, 2024)
Momentum is one of strategy to generate return for profit seeker. This research was conducted to see the existence of momentum strategy at the industry level with the object of all stocks on the Indonesia Stock Exchange consists of 880 stocks grouped into 11 industries based on ICB (Industry Classifi- cation Benchmark). Research period start in July 2014 until December 2023. There are 6 industry momentum strategies, 3 strategies to form portfolio quarterly and 3 strategies to form portfolio in each semester. Tests are conducted on mean returns and risk-adjusted returns using the Fama-French Three Factor model. The method of forming an industry momentum portfolio for each strategy is done equally-weighted and value-weighted using the prior month’s market capitalization (t-1). The results show positive alpha values, meaning there is an abnormal return generated in the industry momentum strategy up to 1.9% per month. However, the abnormal return is not statistically signifi- cant, which indicates that the existence of industry momentum cannot be significantly explained on the Indonesian stock market.